ONOMASTIC UNITS OF HYDROPOETHONYM PLACE IN THE SYSTEM (Scientific journal of the Fergana State University, 2023)
Like all nations of the world, the onomastic units that name water-related natural phenomena, water bodies and structures, which are called hydronyms in German and Uzbek languages, form a whole system. If they are used for a poetic purpose in an artistic text, they rise to the level of hydropoetonym. The use of hydropoetonyms is related to the poetic skills of poets and writers. In addition to differentiating, identifying, and recording things like the ocean, sea, river, and lake that exist by themselves in nature, it is observed that when they come in different figurative meanings, each of them creates macro and microsemantic fields.